Saúde mental e manifestação psicossomáticas em profissionais que atuam em um hospital psiquiátrico - Polvarini, Valéria de Morais (2022)
Introduction: Professionals who work in psychiatric hospitals are daily faced with complex situations of intense suffering, which can lead to ergonomic, physical, psychic, and somatic consequences for the worker. Objective: To investigate verbal manifestations of pain symptoms in mental health professionals. Method: This research, of a descriptive and qualitative nature, analyzes the answers given by professionals who work in a psychiatric hospital in the city of São José do Rio Preto, to a semi-structured interview prepared by the researcher. The data obtained were transcribed in full, analyzed, and categorized according to the guiding axes - the psychiatric hospital, health and pain, and the professionals' quality of life. Results and Discussion: We considered factors such as violence, overload, working conditions and job satisfaction, which may affect mental health professionals in some way, resulting in physical and mental illness, painful complaints and other psychosomatic manifestations. The performances required by the job may cause the body to appear as the main point of impact of harm at work. Final considerations: The present study observed that mental health professionals working in psychiatric institutions presented psychosomatic symptoms, illness, and physical and mental impairment.